Evaluate the expression: 6 - |-4| + 3 × |-2|

Answers

Answer 1
Answer: The bars with some of the numbers mean the those number MUST be positive.

So: 6 - 4 + 3 x 2 = 2 +6 = 8


Answer 2
Answer: 6 - 4 + 3 × 2 = 2 + 6 = 8

Related Questions

Subtract and simplify. (14x^2+8)-(6x^2+5x-1)
A can of 3 tennis balls sells for $2. If Sal spent more than $24 on tennis balls, which inequality can be used to find n, the number of tennis balls Sal could have bought? Two-thirds n greater-than 24 Three-halves n greater-than 24 2 n greater-than 24 3 n greater-than 24.
What's the gcf of 26?
Find the nth term, a n, of the given arithmetic sequence. a^1 = 75, d = –8, n = 11a. 742 c. 155 b. –13 d. –5
Kwikset Enterprises sold 300 shares of stock at $12.34 per share. The underwriting commission was 5.8%. To the nearest cent, how much did Kwikset Enterprises make on its sale of stock, after subtracting the underwriting commission?

Mike bungee jumped from a building with eight stories. Each story was 15 4/5 feet in height. How tall was the building?

Answers

126 2/5 i multiplied them separately and added the two products together

3 3\10 divided by 1 4\7

Answers

Answer:

First, let's convert the mixed numbers into improper fractions:

3 3/10 = (3 * 10 + 3)/10 = 33/10

1 4/7 = (1 * 7 + 4)/7 = 11/7

Now, we can divide the two fractions:

33/10 ÷ 11/7

To divide fractions, we need to multiply the first fraction by the reciprocal of the second fraction. The reciprocal of 11/7 is 7/11.

So, the division becomes:

33/10 * 7/11

Next, multiply the numerators (top numbers) together and the denominators (bottom numbers) together:

(33 * 7) / (10 * 11) = 231/110

Finally, simplify the fraction, if possible. In this case, we can divide both the numerator and denominator by their greatest common divisor, which is 11:

231/110 = (231 ÷ 11)/(110 ÷ 11) = 21/10

Therefore, 3 3/10 divided by 1 4/7 is equal to 21/10.

The cat is a high speed catamaran auto ferry that operates between city A and city B the cat can make the trip in about 2 and 1/2 hours at a speed of 53 mph how far apart are city A and city B

Answers

The city A and city B are 132.5 miles apart.

What is multiplication?

Multiplication is a mathematical arithmetic operation. It is also a process of adding the same types of expression for some number of times.

Example - 2 × 3 means 2 is added three times, or 3 is added 2 times.

Given:

The cat is a high speed catamaran auto ferry that operates between city A and city B the cat can make the trip in about 2 and 1/2 hours at a speed of 53 mph.

That means,

the distance between the cities are,

= 53 x 2.5

= 132.5 miles.

Therefore, the distance is 132.5 miles.

To learn more about the multiplication;

brainly.com/question/19634536

#SPJ2

If the CAT operates with a constant speed of 53 mph (which means it beats 53 miles in one hour) and makes a trip in about 2 and 1/2 hours, we just have to multiply 53 by 2 1/2 to find out the overall distance it's beating in that time:

53 * 2 1/2 =
= 53 * 2.5 =
= 132.5

Answer: City A is about 132.5 miles from city B.

What is the factored form of 2x3 + 4x2 – x?a) 2x ( x^2 + 2x + 1)
b) x (2x^2 + 4x + 1)
c) 2x (x^2 + 2x - 1)
d) x (2x^2 + 4x -1)

Answers

To solve this question, we need to write this equation in simplified form.
So, Taking the GCF from 2x³ + 4x² - x,  
x is divisible by all of them so our new equation will be,

x ( 2x² + 4x - 1)
Correct option is D.

Hope this helped you.. :)

D= 5/6 (F+G) solve for G

Answers

D = 5/6(F + G)
(6 * D)/5 = F + G
(6 * D - F)/5 = G

Expand (2x-3y+3)^2

PLEASE HELP!!

Answers

Answer:

Step-by-step explanation:

(x+ y + z)² = x² +y² + z² + 2xy +2yz + 2zx

Here, x = 2x   ; y = -3y  & z = 3

(2x - 3y + 3)² = (2x)² + (-3y)² + 3² + 2(2x)(-3y) + 2(-3y)3 + 2*3*(2x)

                    = 4x² + 9y² + 9  - 12xy - 18y + 12x

Answer:

4x² + 9y² + 12x - 18y - 12xy + 9

Step-by-step explanation:

Given

(2x - 3y + 3)² = (2x - 3y + 3)(2x - 3y + 3)

Each term in the second factor is multiplied by each term in the first factor, that is

2x(2x - 3y + 3) - 3y(2x - 3y + 3) + 3(2x - 3y + 3)

Distribute the 3 parenthesis

= 4x² - 6xy + 6x - 6xy + 9y² - 9y + 6x - 9y + 9 ← collect like terms

= 4x² + 9y² + 12x - 18y - 12xy + 9